The formation of environmentally safety land use in agricultural enterprises - Степаненко, Тетяна Олександрівна (Technology audit and production reserves, 2015)
In modern conditions before each landowner and land user raises questions of environmental and economic effects of business activities, finding the most reasonable in terms of environmental protection, forms and methods of economic and environmentally sustainable use of agricultural land. One solution to these issues is the introduction of ecologically land. Environmentally safety agricultural land use land use process that involves the conservation and improvement of soil fertility through the use of measures for the land protection, which include: improving the structure of agricultural land and acreage, soil-tilling land, evidence-based standards of fertilizer applying, mainly use of biological methods of plant protection and modern agricultural machinery. Theoretical foundations of the formation and development of environmentally safety use of agricultural land are investigated. The ways of rational use and protection of land resources and reproduction of land resource potential of agricultural enterprises are grounded. It is established that environmentally safety agricultural land use requires consideration of territorial, economic, environmental and social factors that significantly affect the condition of land, their performance, and at the same time the efficiency of agricultural enterprises.